Diverticular disease in Scotland: 2000–2010. (20th March 2015) - Paterson, H. M.; Arnott, I. D.; Nicholls, R. J.; Clark, D.; Bauer, J.; Bridger, P. C.; Crowe, A. M.; Knight, A. D.; Hodgkins, P.; Solomon, D.; Dunlop, M. G.
Abstract: Aim: Symptomatic diverticular disease (DD) may be increasing in incidence in western society particularly in younger age groups. This study aimed to describe hospital admission rates and management for DD in Scotland between 2000 and 2010. Method: Data were obtained from the Scottish Morbidity Records (SMR01). The study cohort included all patients with a hospital admission and a primary diagnosis of DD of the large intestine (ICD‐10 primary code K57). Results: Scottish NHS hospitals reported 90 990 admissions for DD (in 87 314 patients) from 2000 to 2010. The annual number of admissions increased by 55.2% from 6591 in 2000 to 10, 228 in 2010, an average annual increase per year of 4.5%. Most of the increase attributable to DD was due to elective day cases (3618 in 2000; 6925 in 2010) a likely consequence of a greater proportion of the population accessing colonoscopy over that time period. There was an 11% increase in inpatient admissions (2973–3303), 60% of these patients being women. Admissions in younger age groups increased proportionally in the later years of the study, and there was an association between DD admissions and greater deprivation. Despite an increase in complicated DD from 22.9% in 2000 to 27.1% in 2010 and a 16.8% increase in emergency inpatient admissions, the rate of surgery fell during the period of study. Conclusion: This report supports findings of other population‐based studies of western countries indicating that DD is an increasing burden on health service resources, particularly in younger age groups.